Sugar-lowering drugs for type 2 diabetes mellitus and metabolic syndrome - review of classical and new compounds: Part-I - Vieira, Raquel (2019)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia together with disturbances in the metabolism of carbohydrates, proteins and fat, which in general results from an insulin availability and need imbalance. In a great number of patients, marketed anti-glycemic agents have shown poor effectiveness in maintaining a long-term glycemic control, thus being associated with severe adverse effects and leading to an emerging interest in natural compounds (e.g., essential oils and other secondary plant metabolites, namely, flavonoid-rich compounds) as a novel approach for prevention, management and/or treatment of either non-insulin-dependent diabetes mellitus (T2DM, type 2 DM) and/or Metabolic Syndrome (MS). In this review, some of these promising glucose-lowering agents will be comprehensively discussed.